Effect of Nitrogen Doping on Structural, Electrical, and Optical Properties of CuO Thin Films Synthesized by Radio Frequency Magnetron Sputtering for Photovoltaic Application. (28th June 2021) - Patwary, Md Abdul Majed; Ohishi, Miho; Saito, Katsuhiko; Guo, Qixin; Yu, Kin Man; Tanaka, Tooru
Abstract : Effects of N-doping in CuO thin films synthesized in an ambient of Ar, O2 and N2 using a pure Cu target by radio frequency (RF) magnetron sputtering are investigated systematically with the detailed analyses on the structural, electrical, and optical properties of the thin films. A strong N-doping effect was observed on the composition, morphology, and functional properties of the resulting CuO films with the change of N2 gas flow rate ( R N 2 ). X-ray diffraction (XRD) and Raman spectroscopy confirmed the formation of the single phase of N- doped CuO at the studied R N 2 from 0 to 4 sccm. The atomic force microscopy (AFM) showed sub-rounded shape of the CuO grains. N concentrations in the N-doped CuO thin films were increased almost linearly from 1.3 × 10 20 to 3.3 × 10 20 cm −3 which was investigated and confirmed by SIMS. Optical absorption results of both undoped and N-doped CuO films demonstrated a direct transition at E g = 1.52 ∼ 1.56 eV with high absorption coefficient. All the undoped and N-doped CuO thin films showed p-type conductivity, and the resistivity of N-doped CuO decreases from 810 to 18 Ωcm with the increase of R N 2 from 0 to 4 sccm. These results demonstrate the p-type conductivity control by N-doping, leading to the potential of N-doped CuO as an absorber material for solar cells.